A Class of Vector Lyapunov Functions for Stability Analysis of Nonlinear Impulsive Differential Systems. (5th May 2014) - Qunli, Zhang
Abstract : A novel and effective approach to stability of the solutions of nonlinear systems with impulsive effect is considered. The investigations are carried out by means of a class of vector Lyapunov functions and differential inequalities for piecewise continuous functions. Simulation examples are given to illustrate the presented results.